2010
DOI: 10.1007/s00415-010-5578-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot phase of a European MS register

Abstract: The MS-ID (Multiple Sclerosis Information Dividend) project was initiated by the European Multiple Sclerosis Platform (EMSP) in 2007 in order to identify and address major inequalities of MS treatment and care and thus eliminate disparities across the EU. One major approach to reach these goals in the longer term is the implementation of a European MS register for MS. The feasibility of an EU MS register was piloted among five countries (Germany, Iceland, Poland, Romania and Spain). Each country liaised with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
1
11
0
2
Order By: Relevance
“…In addition, we ask regulators and funders to consider the relevance of the placebo arm and the assimilation of more long-term data on the therapy options available. In this regard, we support the European Commission’s consideration for a patient registry [4]. …”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, we ask regulators and funders to consider the relevance of the placebo arm and the assimilation of more long-term data on the therapy options available. In this regard, we support the European Commission’s consideration for a patient registry [4]. …”
Section: Resultssupporting
confidence: 69%
“…Current medications slow the accumulation of disability in MS and reduce the frequency of relapses by modulating or (selectively) suppressing the patient’s immune system [2]. Although scientific evidence exists to show that early access to effective treatment and care is cost-efficient to society and has a meaningful impact on the quality of life of patients [3], significant disparity still exists between and within countries in the standard of treatment offered to people with MS [4]. There also remains a lack of awareness and education of MS in general among healthcare professionals, patients, and the general public [5–8].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe around 500,000 people suffer from MS [74]. MS is a chronic autoimmune disease that is characterized by demyelination of axons of the central nervous system caused by autoreactive T-cells and demyelinating antibodies.…”
Section: Mk As a Modulator Of The Inflammatory Responsementioning
confidence: 99%
“…The use of each approach probably depends on social and health policy system in each country [28]. The role of policy systems in disparities within Europe is mentioned in a very recent study [29] that compared treatment and care of MS in chosen six countries with different geography, culture, and economical and politic systems. Prodiner et al 2010 [30] confirmed that policy factors influence participation in work or social life and recommended the development of participation outcome measurements.…”
Section: Discussionmentioning
confidence: 99%